Study of Hall Effect Sensor and Variety of Temperature Related Sensitivity - Awadia Ahmed Ali; Guo Yanling (Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
Hall effect sensors are used in many applications because they are based on an ideal magnetic field sensing technology. The most important factor that determines their sensitivity is the material of which the sensor is made. Properties of the material such as carrier concentration, carrier mobility and energy band gap all vary with temperature. Thus, sensitivity is also influenced by temperature. In this study, current-related sensitivity and voltage-related sensitivity were calculated in the intrinsic region of temperature for two commonly used materials, i.e. Si and GaAs. The results showed that at the same temperature, GaAs can achieve higher sensitivity than Si and it has a larger band gap as well. Therefore, GaAs is more suitable to be used in applications that are exposed to different temperatures.